EVALUATION OF PRODUCT QUALITY: INDICATORS AND METHODS - Svitlana Gutkevych; Yurii Safonov; Oleh Holovko (Baltic Journal of Economic Studies, 2025)
The present article focuses on the economic approach to product quality management, which seeks to achieve an economic effect by comparing costs and benefits. The article evaluates the effectiveness and efficiency of product quality management based on market, financial, social, and other factors. A range of approaches to quality management efficiency are identified, including economic, scientific and technical, resource, social, and environmental. Indicators are utilised to evaluate the efficacy of the product quality management process, and these indicators may be absolute or relative. The selection of quality indicators is contingent upon the unique characteristics of the product or service in question, with consideration given to both consumer requirements and company policy. The article further proposes a classification scheme of product quality indicators, encompassing the manner of expression, the scope of application, the number of assessed properties, and the stages of determining indicators. The article goes on to discuss the particular complexities involved in evaluating the effectiveness of activities in the printing industry. The quality of the publication produced by publishing and printing enterprises is the result of the editorial process, the publishing processing and the polygraphic execution. The article proposes a set of quality indicators for printing enterprises, which includes product and service quality. A variety of methods and indicators are employed to evaluate the quality of manufactured products, including the absolute, relative, prospective, and optimal levels of quality. The article under discussion herein sets forth a range of approaches to the evaluation of costs associated with quality assurance, proposing the utilisation of a system of indicators for the purpose of evaluating quality. The proposed methods encompass the differential, complex, and mixed approach. The article proposes evaluating the effectiveness of quality control and the organisational and technological readiness of the enterprise, as well as its solvency, personnel support and information support, in order to assess the quality of physical printed products and printing services provided by the company. It also suggests evaluating management effectiveness at three levels: the manufacturing enterprise; the customer of printing services; and the end user of printed products. The article under discussion herein sets out to explore the use of rating systems in the evaluation of the effectiveness of product quality management. In this regard, the balanced scorecard system (BSS) is presented as an alternative to traditional financial analytical evaluation indicators.